2011
DOI: 10.1186/1748-5908-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Implementing accountability for reasonableness framework at district level in Tanzania: a realist evaluation

Abstract: BackgroundDespite the growing importance of the Accountability for Reasonableness (A4R) framework in priority setting worldwide, there is still an inadequate understanding of the processes and mechanisms underlying its influence on legitimacy and fairness, as conceived and reflected in service management processes and outcomes. As a result, the ability to draw scientifically sound lessons for the application of the framework to services and interventions is limited. This paper evaluates the experiences of impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 27 publications
3
76
3
2
Order By: Relevance
“…Where it has been used to evaluate priority-setting decisions, it facilitated the identification of key areas that needed improvement [21,22]. Daniels and Sabin, who developed the framework, suggest that 'accountability for reasonableness' is relevant to pharmaceutical priority setting:…”
Section: Introductionmentioning
confidence: 99%
“…Where it has been used to evaluate priority-setting decisions, it facilitated the identification of key areas that needed improvement [21,22]. Daniels and Sabin, who developed the framework, suggest that 'accountability for reasonableness' is relevant to pharmaceutical priority setting:…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the papers attributed the failure to meet this condition to constant failure by decision makers to provide rationale for decisions made ( Bravo Vergel & Ferguson, 2006; Bukachi et al ., 2014; Gibson et al ., 2006; Maluka et al ., 2010a; Zulu et al ., 2014). For example, Bravo Vergel & Ferguson (2006), observed that though the primary care trusts in England made some effort to communicate priority setting policies through general practitioners and in some few instances through flowcharts and leaflets, the provision of rationale for the decisions were never given.…”
Section: Resultsmentioning
confidence: 99%
“…However, few realist evaluations have been conducted in a low-income country context [23][24][25][26][27][28][29][30] and the authors are cautious of methodological issues that may arise. Notably, as experienced during IPT development, limited reports and literature document the context or contextual influences in which a programme operates, and though the researcher is to complete additional searches to highlight such concepts, contextual information may be missing or overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, realist evaluations are increasingly being used to inform complex health interventions, [21][22][23] with an emerging application in lowincome and middle-income countries. [23][24][25][26][27][28][29] Advocates note that their methodological design better enables the evaluation of complex health interventions compared to quasi-experimental designs. 22 30 Realist evaluations A form of theory-based evaluation, realist evaluations aim to identify 'what works, for whom, and under what circumstances', by developing context-mechanismoutcome configurations (CMOCs).…”
Section: Introductionmentioning
confidence: 99%